Dampak spiritualitas, motivasi, dan stres kerja terhadap kinerja dosen IAIN Salatiga selama masa work from home - Sukma, Fajar Aditiya; Trishananto, Yudha (Nur Science Institute, 2022)
This study aims to determine the influence of spirituality in the workplace and motivation on lecturer performance during WFH, with work stress as an intervening variable. This research uses quantitative methods by processing primary data obtained through distributing questionnaires to other Salatiga lecturers. The samples taken were from 81 respondents using a simple random sampling technique. The method used is multiple linear regression. The test results obtained results: spirituality, motivation, and work stress had a significant positive effect on lecturer performance during the work-from-home period at IAIN Salatiga